The slowdown of increasing groundwater storage in response to climate warming in the Tibetan Plateau - Longhuan Wang; Binghao Jia; Xing Yuan; Zhenghui Xie; Kun Yang; Jiancheng Shi (npj Climate and Atmospheric Science)
Abstract The change of groundwater storage (GWS) on the Tibetan Plateau (TP) is vital for water resources management and regional sustainability, but its estimation has large uncertainty due to insufficient hydrological measurements and diverse future climate scenarios. Here, we employ high-resolution land surface modeling, advanced satellite observations, global climate model data, and deep learning to estimate GWS changes in the past and future. We find a 3.51 ± 2.40 Gt yr−1 increase in GWS from 2002–2018, especially in exorheic basins, attributed to glacier melting. The GWS will persistently increase in the future, but the growth rate is slowing down (0.14 Gt yr−1 for 2079–2100 under a high emission scenario). Increasing GWS is projected over most endorheic basins, which is associated with increasing precipitation and decreasing shortwave radiation. In contrast, decreasing GWS is projected over the headwaters of Amu Darya, Yangtze, and Yellow river basins. These insights have implications for sustainable water resource management in a changing climate.